2014
DOI: 10.3109/07420528.2014.987295
|View full text |Cite
|
Sign up to set email alerts
|

24-hour pattern of falls in hospitalized and long-term care institutionalized elderly persons: A systematic review of the published literature

Abstract: Falls are common among the elderly > 65 years of age and can result in both serious trauma and costly medical care. The epidemiology of falls in the elderly typically focuses on identifying contributory exogenous environmental and endogenous age-related physical, cognitive and other health status factors; however, one potentially important variable seldom considered is time of fall. We sought to determine if falls in hospitalized/institutionalized elderly persons exhibit 24 h and other temporal patterns, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“… 38 In the literature, data on 24-hour fall patterns in the hospital setting are inconsistent. 39 Among demographic and clinical characteristics of patients who experienced falls, advanced age, history of falls, dementia, and poor functional state were, as it would be expected from other studies, 36 factors predictive of falls. Lower BMI appeared to be another risk factor in our study group.…”
Section: Discussionmentioning
confidence: 63%
“… 38 In the literature, data on 24-hour fall patterns in the hospital setting are inconsistent. 39 Among demographic and clinical characteristics of patients who experienced falls, advanced age, history of falls, dementia, and poor functional state were, as it would be expected from other studies, 36 factors predictive of falls. Lower BMI appeared to be another risk factor in our study group.…”
Section: Discussionmentioning
confidence: 63%
“…A recent systematic review suggests a peak 24-hour pattern of fall incidence among sample cohorts in institutional settings. 14 In addition, since many patients are admitted to the nursing home with newly prescribed medications (many of which increase fall risk), routine medication review and reduction is hypothesized to be critical for this population.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature concluded that the incidence of falls in older persons follows a circadian variation. 20 A better understanding of conditions in which falls occur can lead to the implementation of countermeasures (such as adjusting the scheduling of hospital staff, or changing the timing of anti-hypertensive medication if falls are related to undesirable circadian patterns of blood pressure and/or heart rate). This includes knowing the times of the day, days of the week, and times of the year when falls are more likely to occur at home or in the hospital.…”
Section: Aging Circadian Rhythms and Fallsmentioning
confidence: 99%
“…Falls were found to be more frequent on Fridays, Sundays, and Mondays compared with Tuesdays, and were more frequent in winter and spring. 20 Circadian rhythms are genetically anchored. Their endogenous period differs only slightly, but statistically significantly, from exactly 24 hours.…”
Section: Chronobiological Interventionsmentioning
confidence: 99%